MEDIA KOMUNIKASI SEBAGAI AKSES LAYANAN REFERENSIVIRTUAL DI PERPUSTAKAAN UNIVERSITAS INDONESIA - Rahmi, Lailatur (Buletin Al-Turas, 2019)
AbstractThe Reference Service is one of the library services designed to assist the users of the library in meeting their information needs. The development of reference services is, especially, important in the tertiary educational institutions. The growth of incredible information and technological developments decline the number of users of the printed reference collections ; there are pros and cons when it comes to the technology that, supposedly, make things easier and practical. The study aims to describe the usefulness of communication media in virtual reference services at the University of Indonesia Library. The results of the study illustrate that the University of Indonesia library has provided communication media as access to virtual reference services through various communication media due to the influence of the development of technological sophistication